A simple method using CRISPR-Cas9 to knock-out genes in murine cancerous cell lines - Airi Ishibashi (Nature Portfolio, 2020)
Abstract CRISPR-Cas9 system can be used to generate knock-out cancer cell lines. An insertion or deletion induced by a single guide RNA (gRNA) is often used to generate knock-out cells, however, some cells express the target gene by skipping the disrupted exon, or by using a splicing variant, thus losing the target exon. To overcome this unexpected expression of the target gene, almost the entire gene can be swapped with a selection marker. However, it is time-consuming to create a targeting vector which contains 5′ and 3′ homology arms flanked by a selection marker. Here, we developed a simple and easy method called SUCCESS (Single-strand oligodeoxynucleotides, Universal Cassette, and CRISPR/Cas9 produce Easy Simple knock-out System), to knock-out a target gene without constructing a targeting vector. Our method removed the targeted large genomic region by using two pX330 plasmids encoding Cas9 and gRNA, two 80mer single strand oligodeoxynucleotides (ssODN), and a blunt-ended universal selection maker sequence in B16F10 murine cancer cell and ID8 murine ovarian cancer cell. SUCCESS generated knock-out clones in two murine cancer cell lines by homozygous deletion of the target genomic region, and without constructing targeting vectors. Thus, our method can be widely applied to generate homozygous knock-out cell lines, as well as knock-in cell lines.